Bodyland: Honeybees and the legitimacy of (human) presence in postwar Angola. (20th January 2022) - BAPTISTA, JOÃO AFONSO
ABSTRACT: The Angolan village of Cusseque, established during the country's civil war, lost its military purpose when the conflict ended in 2002. The village's neighbors assumed that Cusseque's remaining residents would leave; most stayed. They have since fought to legitimize their presence. Fieldwork with Cusseque residents helps illuminate why they assert their merging with the land—a merging that I call bodyland —through the agency of honeybees. These men and women exert a compelling body politics, one that is subject to the more‐than‐human agencies that dissolve the contours of the human. Moreover, Cusseque's residents contribute to anthropological discussions about human‐land relations by blending the question of the human with that of the land. They defy pervasive humanist regimes in which the legitimacy of human presence is dissociated from the interdependence between body and land. [ human‐land relationship, legitimacy, transcorporeality, honey, honeybees, postwar, body politics, Angola ] Abstract : A aldeia angolana de Cusseque, estabelecida durante a guerra civil nacional, perdeu o seu objetivo militar quando o conflito terminou, em 2002. Os vizinhos desta aldeia assumiram que os moradores de Cusseque iriam embora. Mas a maioria ficou. Estes homens e estas mulheres têm desde então lutado para legitimar a sua presença em Cusseque. O meu trabalho de campo na região ajudou‐me a clarificar a razão pela qual eles e elas afirmam que resultam da fusão com a terra—uma fusão a que chamo corpoterra —através da ação das abelhas. Em Cusseque, as pessoas exercem uma política corporal vinculada às ações mais‐do‐que‐humanas que dissolvem os contornos do ser humano na terra. Contribuem assim para discussões antropológicas sobre a relação entre as pessoas e a terra, misturando a questão do ser humano com a questão da terra. Fundamentalmente, os residentes de Cusseque desafiam os regimes humanistas em que a legitimidade da presença humana é dissociada da interdependência entre o corpo e a terra. [ relação humano‐terra, legitimidade, transcorporeidade, mel, abelhas, pós‐guerra, política corporal, Angola ]